Mapping cooperation: insights into Colombia's humanitarian response to migration from Venezuela - Romero, Liss Dayana; Padilla, Jose J.; Palacio, Katherine; Frydenlund, Erika (Frontiers in Human Dynamics, 2024)
This study examines organizational cooperation in the humanitarian response to the migration situation from Venezuela to Colombia. Since 2015, Colombia has received approximately 2.9 million displaced Venezuelans. Our research, based on interviews and web scraping, aims to identify key organizations and actors and their relationships. We used Social Network Analysis to establish collaborative partnerships and strategies employed by these organizations to address the challenges posed by the migration situation. Results show that cooperation occurred through mediated channels, where established NGOs collaborated via coordination mechanisms established by international nongovernmental organizations (INGOs), often involving diaspora volunteer-based organizations and through ad-hoc coordination. We also identified organizations specializing in specific activities often exhibited limited coordination with others operating in the same sector. Lastly, results suggest that coordination mechanisms played a crucial role in driving activities and facilitating the diversification of responses, partly through the allocation of financial resources.